Optimization of infrared-assisted extraction of Bletilla striata polysaccharides based on response surface methodology and their antioxidant activities. (5th September 2016) - Qu, Yan; Li, Chunxue; Zhang, Chen; Zeng, Rui; Fu, Chaomei
Highlights: Infrared-assisted extraction is used for the first time to isolate polysaccharides from Bletilla striata (Thunb.) Reichb.f.(BSP) based on response surface methodology and a Box-Behnken design. The structures of BSP made by freeze drying technique were observed by scanning electron microscopy. Tertiary structure determination indicated Bletilla striata polysaccharides had triple-helical conformation. Fourier transform infra-red spectroscopy characterization revealed that BSP produced typical absorption peaks. The antioxidant activities of Bletilla striata polysaccharides were measured for the first time. Abstract: Bletilla striata polysaccharides (BSP) have attracted extensive research interest due to their potential medical application. Herein, infrared-assisted technique is employed for the first time to extract BSP from B. striata (Thunb.) Reichb.f. based on a Box-Behnken design (BBD) and response surface methodology, with the optimum extraction parameters as follows: 75 °C extraction temperature, 2.5 h extraction time; and water to solid ratio (53 ml/g). Based on it, 43.95 ± 0.26% yield of crude BSP was obtained. Subsequently, crude BSP was further decolorized, deproteinized, freeze-dried, and purified by a DEAE-52 cellulose column. Furthermore, the micro-structure and a triple-helical structure of BSP were characterized. Fourier transform infrared spectra confirmed its polysaccharide characterization via typical peaks. In addition, the significant in vitro antioxidant profiles of BSP were demonstrated by superoxide anion radical-scavenging assay, hydroxyl radical scavenging assay, DPPH free radical scavenging activity and chelation of ferrous ions. Taken together, this study provide an efficient extraction technique for BSP as a promising natural antioxidant.